Pengaruh Teknik Relaksasi Lima Jari Terhadap Intensitas Nyeri Pada Pasien Post Operasi Sectio Caesarea Di RSIA Murni Teguh Rosiva Medan - Mulyana, Sri; Simanullang, Rostime Hermayerni (STIKes Murni Teguh, 2025)
Physically, caesarean section causes pain in the abdomen, this pain comes from the surgical wound. Caesarean section delivery has a higher pain level of around 27.3%, compared to the pain level of normal labor which is only around 9%. If pain in post-operative patients is not treated immediately, it will result in the patient's rehabilitation process being delayed, the patient's hospitalization being longer, the complication rate being high and requiring more costs. Objective: to analyze the effect of the five fingers relaxation technique on pain intensity in post-operative caesarean section patients at RSIA Murni Teguh Rosiva Medan. This research used quantitative methods with a quasi-experimental with a nonequivalent control group design. The sampling technique used total sampling, and the instrument used the five fingers relaxation technique and an observation sheet. Mann-Whitney test to analyze data in this study. This study showed that there is an influence of the Five Fingers Relaxation Technique on Pain Intensity in Post-Caesarean Section Surgery Patients at RSIA Murni Teguh Rosiva Medan, with a p-value = 0.001 or (α < 0.05). It is concluded that there is an effect of the five fingers relaxation technique on pain intensity in post-operative caesarean section patients at RSIA Murni Teguh Rosiva Medan. It is hoped that the five-fingers relaxation technique can be applied as a non-pharmacological therapy. It is recommended for further researchers to add a larger number of samples.